Advanced materials and engineering materials VI : 6th ICAMEM : selected, peer reviewed papers from the 6th International Conference of Advanced Materials and Engineering Materials (ICAMEM), March 11-12, 2017, Singapore - Kida, Katsuyuki; Mizobe, Koshiro; International Conference on Advanced Materials and Engineering Materials 2017 : Singapore) (Zurich, Switzerland : Trans Tech Publications, Ltd, 2017)
This book consists from papers by results of the 6th International Conference of Advanced Materials and Engineering Materials (ICAMEM, 11-12 March, 2017, Singapore). The main topics of this collection are functional ceramics, polymers and composites, structural metals and alloys, modern building materials, nanomaterials, chemical technologies and also various materials processing technologies for goal of modern production. We hope this collection will be useful for many engineers, researchers and academics whose activity related to modern materials and technologies of them processing.Ceramics, Polymers, Composites, Structural Metals and Alloys, Processing Technology, Building Materials, Nanomaterials, Chemical Technology, Chemical GeologyMaterials Science
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed March 29, 2018).
Master record variable field(s) change: 050, 072, 082, 650
Keywords: Materials science -- Congresses; Materials -- Congresses; TECHNOLOGY & ENGINEERING / Engineering (General); TECHNOLOGY & ENGINEERING / Reference; Electronic books; Electronic books